What’s in the Two Envelope Paradox? - Scott, Alexander D.; Scott, Michael (Analysis, 1997)
Focuses on the nature of two envelope paradox. Possibility of probabilistic argument in favor of swapping envelopes; Consideration of pragmatic restrictions on the availability of currency; Specification of particular assumption.